Radiation shielding performances of Na2SiO3 based low-cost micro and nano composites for diagnostic imaging - ŞAHİN, NAZLICAN (Elsevier Ltd, 2021)
The present study deals with determining the gamma-ray shielding parameters of the micro (μ)- Bi2O3, μ−WO3, nano (n)-Bi2O3, and n-WO3 reinforced Na2SiO3 (sodium metasilicate) composites experimentally and theoretically. The study has aimed to compare the size of reinforcing particles on the gamma-ray shielding ability of very low-cost and non-toxic Na2SiO3. In this context, the gamma-ray shielding performances of the samples containing different weight percentages of μ-Bi2O3, μ-WO3, n-Bi2O3, and n-WO3 particles have been evaluated by employing mass attenuation coefficient, half-value layer, and mean free path. The related parameters have been measured experimentally and also calculated by WinXCom. It has been revealed that Na2SiO3 composites having micro and nano-structured Bi2O3 and WO3 particles show good radiation shielding for 81 keV photons. In this respect, among all composites, the Na2SiO3/30% μ-WO3 sample has a promising potential to shield the ionizing radiation utilized in diagnostic imaging such as mammography, conventional X-ray machine, etc. © 2021
Keywords: Bismuth oxide; Mass attenuation coefficient; Nanocomposites; Radiation shielding; Sodium metasilicate; WinXCom